Modification of the Cardiac Renal Angina Index for Predicting Adverse Kidney Events After Pediatric Cardiac Surgery - Melink, Katherine F.; Stanski, Natalja L.; Gorrell, Emily; Alten, Jeffrey A.; Pettit, Kevin A.; Goldstein, Stuart L.; Zang, Huaiyu; Ollberding, Nicholas J.; Basu, Rajit K.; Menon, Shina; SooHoo, Megan; Gist, Katja M. (Journal of the American Heart Association, 2025)
Pediatric cardiac surgery-associated acute kidney injury is common and associated with poor outcomes, but early prediction is challenging. The purpose of this study was to determine the performance of a modified cardiac renal angina index (cRAI) in predicting adverse renal events and whether biomarker integration (urine neutrophil gelatinase-associated lipocalin) enhances cRAI performance. This was a 2-center prospective observational study in children ages 0 to 18 years admitted to the intensive care unit after cardiac surgery. The cRAI was presented as a nomogram using multivariable logistic regression to predict a composite of (1) any postoperative day 2 to 4 acute kidney injury, or (2) mechanical ventilation ≥3 days. The performance of including urine neutrophil gelatinase-associated lipocalin into the nomogram was compared with the model constructed for cRAI alone. Of 476 patients, 129 (27%) experienced the composite outcome, and 191 (40%) were cRAI positive. Patients who were cRAI positive were younger, had higher surgical complexity, a higher mortality rate, and longer intensive care unit length of stay. cRAI predicted the composite outcome with an optimism-corrected area under the receiver operating characteristic curve of 0.82, sensitivity of 0.81 (95% CI, 0.73-0.87), specificity of 0.75 (95% CI, 0.70-0.80), and negative predictive value of 0.91 (95% CI, 0.87-0.94). Incorporating urine neutrophil gelatinase-associated lipocalin improved predictive performance, with an area under the receiver operating characteristic curve of 0.84, sensitivity of 0.84 (95% CI, 0.77-0.90), specificity of 0.79 (95% CI, 0.74-0.83), and negative predictive value of 0.93 (95% CI, 0.90-0.96). The cRAI demonstrates strong predictive performance for adverse renal outcomes. Patients who were cRAI positive had worse outcomes, while the composite outcome was effectively ruled out in patients who were cRAI negative. Urine neutrophil gelatinase-associated lipocalin integration improved predictive performance parameters. cRAI holds potential for cardiac surgery-associated acute kidney injury risk stratification to enrich clinical trial enrollment.